To prevent complications after surgery for stages 1-2 of cervical cancer (Texas Journal of Medical Science, 2025)
Cervical cancer is among the most common malignancies affecting women worldwide, with surgery serving as the cornerstone of treatment for early stages (I–II). Despite advances in surgical techniques and perioperative management, post-surgical complications remain a significant challenge. These include infectious processes, thromboembolic events, lymphatic complications, urinary and sexual dysfunction, and psychological disturbances, which may negatively affect quality of life and long-term prognosis.